Futuristic restoration as a policy tool for environmental justice objectives. Issue 3 (1st March 2022) - Pape, Timothy
Abstract : The United Nations Decade on Ecosystem Restoration promises to educate society on the many ways ecological restoration projects can benefit humankind. One avenue of possibilities for restoration ecology lies with concerns of environmental justice. The concept of futuristic restoration, which posits a paradigm of ecological restoration that is future‐oriented, aligns well with calls for policymakers to address the circumstances, processes, and systems within which environmental inequalities are typically produced. This article offers three policy arenas where futuristic restoration can be employed in order to further environmental justice goals: (1) Land conservation prioritization; (2) Urban development plans; and (3) Mine remediation projects. The temporal dimension of sustainability and how it pertains to restoration projects will also be addressed.